EFEKTIVITAS MODEL MASTER PADA PEMBELAJARAN IPS SISWA KELAS V SD NEGERI PAGOJENGAN 03 (Harmony: Jurnal Pembelajaran IPS dan PKN, 2019)
This research is motivated by low social studies learning achievement andthe lack of independence of Grade V Students of Pagojengan 03 State Elementary School. The low value of students' Social Sciences that is66,88 that is still under the KKM 70.The subject of this research is Grade V Students of Pagojengan 03 State Elementary Schoolin the amount of 32 grade V A students as the experimental groupwho were treated by the MASTER modeland 20 of Grade VBas a control group treated with conventional models. From the results of the calculation of the data analysis of the experimental class independence is greater, that is 48.62%while the control class is lower with value 44,24%and social studies learning achievements in the experimental class, that is76,21%while in the control class, that is35,59%. So, It can be concluded that the use of the MASTER model is effective on the independence and learning achievement of social studies students of VA students at Pagojengan 03 State Elementary School. Penelitian ini dilatarbelakangi oleh rendahnya prestasi belajar IPS dan kurangnya sikap kemandirian siswa kelas V SD Negeri Pagojengan 03. Guru masih menggunakan metode konvensional, dan rendahnya nilai IPS siswa yaitu 66,88 yaitu masih dibawah KKM 70. Tujuan Penelitian ini adalah untuk mengetahui apakah penggunaan model MASTER dalam pembelajaran IPS tema 7 tentang peristiwa dalam kehidupan, materi proklamasi kemerdekaan di kelas V SD Negeri Pagojengan 03Dari hasil perhitungan analisis data kemandirian kelas eksperimen lebih besar yaitu 48,62% sedangkan kelas kontrol lebih rendah dengan nilai 44,24% dan prestasi belajar IPS di kelas eksperimen yaitu 76,21% sedangkan di kelas kontrol yaitu 35,59%. Jadi, dapat disimpulkan bahwa penggunaan model MASTER efektif terhadap kemandirian dan prestasi belajar IPS siswa kelas V A SD Negeri Pagojengan 03.